2022
DOI: 10.48550/arxiv.2204.04451
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Axially Symmetric Transitioning models with Observational Constraints

Abstract: In this study, we have demonstrated the expansion history of an axially symmetric Bianchi type-I model of the universe. Our model as of now presents an accelerating universe, which had been in the decelerating phase in the past. Roles of the two crucial Hubble H(z) and deceleration q(z) parameters are examined. The energy parameters of the universe are estimated with the help of the latest observational Hubble data (46-data points) and Pantheon data (the latest compilation of SNIa with 40 binned in the redshif… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…To observe the compatibility of models with the recent observational data, we will calculate the Hubble parameter H for each model in upcoming sections and compare the corresponding values of H with recent data. Bhardwaj et al [83] presented the observed values of H for 46 different points against redshift parameter z along with their observational error evaluated by using various age approach by different cosmologists presented in the Table 1 as…”
Section: Chi-square Testmentioning
confidence: 99%
See 3 more Smart Citations
“…To observe the compatibility of models with the recent observational data, we will calculate the Hubble parameter H for each model in upcoming sections and compare the corresponding values of H with recent data. Bhardwaj et al [83] presented the observed values of H for 46 different points against redshift parameter z along with their observational error evaluated by using various age approach by different cosmologists presented in the Table 1 as…”
Section: Chi-square Testmentioning
confidence: 99%
“…4. The error bars added to the figure for comparison representing observations given in [83]. The estimated values for different parameters for minimum χ 2 have been computed as n = 1.096, M = 5, β = 0.6, γ = 1, ω = −1/3, DE0 = 0.7 and α is given in Eq.…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Goswami et al [33] employed observational data from 38 H(z) and 581 SN Ia. We employed 46 observational Hubble data points in the red-shift region 0 ≤ z ≤ 2.36 in this work [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%